2021
DOI: 10.1371/journal.pone.0249025
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge, attitudes and practices towards people living with HIV/AIDS in Lebanon

Abstract: Background Up till today, studies carried in Lebanon have focused more on the prevalence of HIV and behaviors and quality of life of infected individuals, however, none of these studies discussed the degree of stigma towards these populations. Therefore, the aim of this study is to measure the rate of stigma in terms of knowledge, attitude and practice towards patients living with Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) (PLWHA) and examine the factors associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
3
13
0
1
Order By: Relevance
“…The findings from our study showed that respondents who did not have Christian faith had lower knowledge and prevention of HIV/AIDS. This is similar to a study done in Ghana [ 25 ] and Lebanon [ 26 ] that revealed that respondents from the Christian faith demonstrated higher knowledge of HIV/AIDS than other religions. The majority (87%) of the Mizoram population are Christian, and the culture is largely influenced by Christianity.…”
Section: Discussionsupporting
confidence: 90%
“…The findings from our study showed that respondents who did not have Christian faith had lower knowledge and prevention of HIV/AIDS. This is similar to a study done in Ghana [ 25 ] and Lebanon [ 26 ] that revealed that respondents from the Christian faith demonstrated higher knowledge of HIV/AIDS than other religions. The majority (87%) of the Mizoram population are Christian, and the culture is largely influenced by Christianity.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have found positive correlations between HIV attitude and behavior ( 32 ). However, in the current study, the participants in this survey are university and college freshmen who have a relatively conservative attitude toward premarital sex, the percentage of respondents who are willing to insist on using condoms during sex is relatively low (59.1%).…”
Section: Discussionmentioning
confidence: 93%
“…This proves that the respondents already understand enough to prevent HIV-AIDS. A good level of knowledge is felt to play an important role in the prevention of HIV-AIDS [15]. Knowledge of HIV status is relatively high in eastern Europe and Central Asia, but treatment coverage and viral suppression are alarmingly low [16].…”
Section: Discussionmentioning
confidence: 99%